The levels of mRNA expressed by gene palF of A. nidulans do not appear to be pH regulated - W Maccheroni Jr.; G S May; N M Martinez-Rossi; A Rossi (Fungal Genetics Reports, 2000)
Although pal genes are putative members of a signaling cascade involved in ambient pH sensing and in the consecutive activation of PacC protein, recent findings show that most of them (palA, B, C, H and I) do not respond to ambient pH at the transcriptional level. Here, we show that mRNA levels of the remainding palF gene are also constant at various growth pH values.